VD_FINDINFO HC / 2012 / 616 vom 27. September 2012 - VD Tribunal cantonal (2012)
ASSISTANCE JUDICIAIRE, DROIT D'ÊTRE ENTENDU | 29 al. 2 Cst., 29 al. 3 Cst., 117 CPC (CH), 121 CPC (CH), 319 let. b ch. 1 CPC (CH), 322 al. 1 CPC (CH)